Improving laboratory animal genetic reporting: LAG-R guidelines - Teboul, Lydia; Amos-Landgraf, James; Benavides, Fernando J; Birling, Marie-Christine; Brown, Steve D M; Bryda, Elizabeth; Bunton-Stasyshyn, Rosie; Chin, Hsian-Jean; Crispo, Martina; Delerue, Fabien; Dobbie, Michael; Franklin, Craig L; et al. (Nature communications, 2024)
The biomedical research community addresses reproducibility challenges in animal studies through standardized nomenclature, improved experimental design, transparent reporting, data sharing, and centralized repositories. The ARRIVE guidelines outline documentation standards for laboratory animals in experiments, but genetic information is often incomplete. To remedy this, we propose the Laboratory Animal Genetic Reporting (LAG-R) framework. LAG-R aims to document animals' genetic makeup in scientific publications, providing essential details for replication and appropriate model use. While verifying complete genetic compositions may be impractical, better reporting and validation efforts enhance reliability of research. LAG-R standardization will bolster reproducibility, peer review, and overall scientific rigor.
Keywords: Animals, Laboratory; Animal Experimentation; směrnice jako téma; Reproducibility of Results; výzkumný projekt; experimenty na zvířatech; reprodukovatelnost výsledků; biomedicínský výzkum; Research Design; Animals; laboratorní zvířata; zvířata; Biomedical Research; Guidelines as Topic